125 GeV Higgs decay with lepton flavor violation in the μνSSM *Supported by Major Project of NNSFC (11535002) and NNSFC (11275036, 11647120), the Open Project Program of State Key Laboratory of Theoretical Physics, Institute of Theoretical Physics, Chinese Academy of Sciences, China (Y5KF131CJ1), the Natural Science Foundation of Hebei province (A2013201277, A2016201010, A2016201069), Hebei Key Lab of Optic-Electronic Information and Materials, and Midwest Universities Comprehensive Strength Promotion Project. (April 2017) - Zhang 张, Hai-Bin 海斌; Feng 冯, Tai-Fu 太傅; Zhao 赵, Shu-Min 树民; Yan 阎, Yu-Li 玉立; Sun 孙, Fei 飞
Abstract: Recently, the CMS and ATLAS collaborations have reported direct searches for the 125 GeV Higgs decay with lepton flavor violation, h → μ τ . In this work, we analyze the signal of the lepton flavour violating (LFV) Higgs decay h → μ τ in the μ from ν Supersymmetric Standard Model (μ ν SSM) with slepton flavor mixing. Simultaneously, we consider the constraints from the LFV decay τ → μ γ, the muon anomalous magnetic dipole moment and the lightest Higgs mass around 125 GeV.